2017
DOI: 10.9734/bjpr/2017/33210
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Hepatoprotective Potentials of Methanol Leaf Extract of Arachis hypogea

Abstract: The anti-inflammatory and hepatoprotective properties of methanol extract of Arachis hypogea leaves were studied. At 400 mg/kg, the extract significantly suppressed the development of hind paw oedema induced by egg albumin, which compares favorably with a standard antiinflammatory drug aspirin (acetylsalicylate) which at 100 mg/kg inhibits egg-albumin induced rat paw oedema. It was observed that the extract significantly inhibited platelet aggregation in a dose Original Research Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…This study evaluated hepatocellular enzyme activities, hepatic function parameters and antioxidative activity of alloxan-induced diabetic rats administered Acioa barteri extract (ABE). Early detection of diabetes mellitus, lifestyle changes, dietary restriction, and monitoring of blood glucose levels and organ functions including medical interventions remain the major steps towards successful management of diabetes mellitus (Ibeh et al, 2020). While some conventional therapies may not be harmful to the kidneys or liver, studies have shown the beneficial effect of medicinal plants in reducing kidney and liver damage, either alone or in combination with conventional therapy (Nwankpa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study evaluated hepatocellular enzyme activities, hepatic function parameters and antioxidative activity of alloxan-induced diabetic rats administered Acioa barteri extract (ABE). Early detection of diabetes mellitus, lifestyle changes, dietary restriction, and monitoring of blood glucose levels and organ functions including medical interventions remain the major steps towards successful management of diabetes mellitus (Ibeh et al, 2020). While some conventional therapies may not be harmful to the kidneys or liver, studies have shown the beneficial effect of medicinal plants in reducing kidney and liver damage, either alone or in combination with conventional therapy (Nwankpa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%